EXPERTISE RESEARCH IN LANGUAGE TEACHING: SOME EXAMPLES AND SOME ISSUES - Keith Johnson (Indonesian JELT, 2007)
LATEX (for Language Teaching Expertise) is a research group which focuses on expertise studies in areas of language teaching. The paper describes a number of research projects LATEX has been involved in. One set of these are concerned with expertise in task and materials design, considering the procedures so-called experts follow when engaged in these activities. A further project concentrates on materials evaluation and researches how teachers with differing degrees of experience go about the pre-use evaluation of a textbook. Another study comparing the classroom performance of ‘novice’ and ‘expert’ teachers is described. All these studies involve forms of introspection – concurrent verbalization and stimulated recall - and the use of these techniques is regarded as a defining feature of LATEX research. In the final section, two problematical areas related to expertise research are discussed. The first is concerned with how experts are identified. Secondly, a question related to the training of expertise is considered - how central characteristics of expertise can be distinguished from peripheral features, so that training programmes can focus on what is important. Keywords: LATEX, concurrent verbalizationstimulated recall